Interferensi dalam Bahasa Bali: Studi Kasus pada Cerpen Berbahasa Bali: Interference in Balinese: A Case Study of Balinese Short Stories - Sutarma, I Gusti Putu; Sucipta, I Made Darma; Septevany, Elvira; Adnyana, Ida Bagus Artha (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
Language interference in regional literary works is an inevitable phenomenon amidst the multilingual dynamics of its speaking communities. Balinese short stories published in the mass media provide the most concrete opportunity to observe how elements of other languages ??enter and shape the language patterns of contemporary Balinese writers. This phenomenon has direct implications for the preservation of Balinese as a regional language in the global era. This study employs a qualitative descriptive approach, utilizing primary data in the form of Balinese short stories published in newspapers. Data were collected through a listening method with note-taking techniques, analyzed using the matching and distribution method, and presented using formal and informal methods. The theoretical basis used is Applied Sociolinguistics Theory regarding language interference. The interference found originates from two language groups: internal interference from Indonesian and external interference from English. From a linguistic perspective, interference occurs at the vocabulary and phrase level. Factors triggering interference include the speaker's bilingualism, the lack of appropriate lexical equivalents in Balinese, the speaker's positive attitude towards other languages, and the influence of developments in the era and media. Interference in Balinese short stories is a logical consequence of intense language contact in the speaker's environment. This phenomenon cannot be completely eliminated, but it can be minimized by strengthening positive attitudes toward Balinese and standardizing accepted loanwords. Interference also poses a challenge to efforts to preserve Balinese amid the pressures of globalization.